Vaccination in children with inherited bleeding disorders: Does the use of plasma an d factor affect the response to the vaccine: An institutional registry. Issue 1 (20th November 2021) - Tasar, Sercin; Tasar, Medine Aysin; Alioglu, Bulent
Abstract: Introduction: We aimed to evaluate the vaccine seroconversion of paediatric patients with factor deficiency and to complete the missing vaccines. We also emphasize the importance of variables such as recombinant factor and plasma intake frequency. Material and methods: This prospective observational study includes children between 2 and 17 age diagnosed with inhered factor deficiency. Seroconversion of hepatitis A, hepatitis B, varicella, measles, rubella and mumps vaccines were screened according to Ministry of Health Vaccination Schedule, it was completed if there were seronegative vaccines and the vaccine seroconversion was examined after vaccination approximately 1–6 months. Results: A total of 61 children were included in the study [mean age 11.2±5.1 years (2–18)], 49 (80.3%) were males. Factor VIII deficiency constituted 60.7%, factor XI 14.8%, factor VII 13.1 %, factor IX 9.8%, factor X 1.6% of the cases. None of the children had clinically important injection site complications such as uncontrollable bleeding or gross hematoma and vaccination does not induce the development of inhibitor. Measles antibody positivity was significantly lower in those who received factor 3 or 4 days times a week compared to those who received it when necessary (p = .049). Discussion and conclusion: This is the first study evaluating the vaccine conversion patients with inherited factor deficiency receiving plasma and plasma derived factor concentrates. It should be considered that children with haemophilia and their families may have vaccination hesitancy; therefore, follow‐up of these patients should include a specified vaccination program to ensure adequate immunization of these patients.